Microarray analysis of lexA gene deletion mutant of deep-sea bacterium Shewanella piezotolerans WP3 at low-temperature and high-pressure - Jian, Huahua (Genom Data, 2015)
Addressing DNA lesion, the SOS response is conserved in bacterial domain and governed by DNA binding protein LexA, which have been well characterized in model microorganism such as Escherichia coli. However, our understanding of the roles of SOS pathway in deep-sea bacteria is limited. To indentify the composition of SOS regulon and function of LexA, we performed whole genome transcriptional profiling using a custom designed microarray which contains 95% open reading frames of Shewanella piezotolerans WP3. Here we describe the experimental procedures and methods in detail to reproduce the results (available at Gene Expression Omnibus database under GSE66790) and provide resource to be employed for comparative analyses of SOS response in microorganisms which inhabited in different environments, and thus broaden our understanding of life strategy of bacteria against various environment stresses.